Mobile eye tracking evoked teacher self-reflection about teaching practices and behavior towards students in higher education - Kaminskienė, Lina; Horlenko, Kateryna; Matulaitienė, Jovita; Ponomarenko, Tetiana; Rutkienė, Aušra; Tandzegolskienė-Bielaglovė, Ilona (Frontiers in Education, 2023)
The study is based on the concept of teacher professional vision, in which professional reasoning plays a crucial role. This study investigates how video with gaze overlay and heatmaps from the mobile eye tracker can support teachers' professional self-reflection and professional vision development in higher education. Four university teachers wore a mobile eye tracker in a segment of one lecture. Their gaze distribution on classroom targets was analyzed together with their reflective comments when watching the recordings of their own behavior in the lecture. The results showed that mobile eye tracking data provided feedback on the distribution of teacher attention in different areas in the classroom and between students. Visualization of gaze distribution as heatmaps allowed teachers to reflect on how they perceived their gaze allocation, as most of them realized that sometimes there was a difference between how they perceived their gaze allocation and how it was captured by the eye tracker. The study revealed where teachers most often diverted their attention, which encouraged them to reflect on why this happened, to think about their professional reasoning and to analyze opportunities for improvement. Therefore, the heatmap analysis based on the data collected with the mobile eye trackers could be used to develop the professional vision of teachers in different educational contexts for engaging students through more balanced attention to every student in the classroom. Implications for using mobile eye tracker recording and gaze distribution heatmaps in video-based professional development for teachers are discussed.